It's Not All in Your Head (or at Least Your Brain): Association of Traumatic Brain Lesion Presence and Location with Performance on Measures of Response Bias in Forensic Evaluation. (30th September 2013) - McBride, Willie F.; Crighton, Adam H.; Wygant, Dustin B.; Granacher, Robert P.; Granacher, Robert P.; Sweet, Jerry J.; Felthous, Alan R.
<x xml:space="preserve">Abstract</x> This study examined the relationship between lesion presence and localization and performance on measures of cognitive response bias, specifically in individuals purporting to have a traumatic brain injury. Ninety‐two participants, all of whom were involved in workers' compensation or personal injury litigation, were administered an extensive neuropsychological battery, including neuroimaging (magnetic resonance imaging and computed tomography), at a neuropsychiatric clinic in Lexington, KY. Those with evidence of intracranial injury on neuroimaging findings were placed in the head injury lesion litigation group and were coded based on the anatomical location and type of intracranial injury. Results demonstrated no significant relationships between lesion location and performance on performance validity tests (PVTs), as well as the Response Bias Scale of the Minnesota Multiphasic Personality Inventory‐2 Restructured Form. Given the lack of research concerning lesions and performance validity tests, this study addresses important questions about the validity of PVTs as specific measures of response bias in patients who have structural changes secondary to traumatic brain injury. Copyright © 2013 John Wiley & Sons, Ltd.